Repercussions of intestinal ostomy on male sexuality: an integrative review - Isabella Felix de Araújo Meira; Fernanda Rios da Silva; Anderson Reis de Sousa; Evanilda Souza de Santana Carvalho; Darci de Oliveira Santa Rosa; Álvaro Pereira (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To analyze scientific productions about the repercussions of intestinal ostomy on male sexuality and discuss its implications for planning nursing care. Method: Integrative literature review conducted in the databases Scientific Electronic Library Online, Latin American and Caribbean Literature in Health Sciences, Sciverse Scopus, Web of Science, Cumulative Index to Nursing and Allied Health Literature and National Library of Medicine and National Institutes of Health, with no pre-established time frame and using the descriptors "sexuality," "ostomy," "colostomy," "men" and "nursing." Results: 21 articles were included to compose the interpretative analysis. Studies have shown that intestinal ostomy can affect male sexuality and reflect negatively on biophysiological, psychoemotional, and sociocultural dimensions. Final Considerations: Through education strategies in programs that follow-up ostomized men from preoperative to rehabilitation, the nurse can assist in adapting to reality, as well as in the quality of life.